2018
DOI: 10.1158/1078-0432.ccr-17-3775
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp63γ/SRC/Slug Signaling Axis Promotes Epithelial-to-Mesenchymal Transition in Squamous Cancers

Abstract: To investigate the regulation of epithelial-to-mesenchymal transition (EMT) in head and neck squamous cell carcinoma (HNSCC) and its importance in tumor invasion. We use a three-dimensional invasive organotypic raft culture model of human foreskin keratinocytes expressing the E6/E7 genes of the human papilloma virus-16, coupled with bioinformatic and IHC analysis of patient samples to investigate the role played by EMT in invasion and identify effectors and upstream regulatory pathways. We identify SNAI2 (Slug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
4
20
0
Order By: Relevance
“…The effect of SLUG on EMP dynamics can also be influenced by upstream regulators of SLUG such as RNF8, YAP, C/EBPδ, miR-151, CBP, RCP, HDAC1, HDAC3, BRD4 and STAT3 [Cheng et al, 2020;Chesnelong et al, 2019;Kuang et al, 2020;Wang et al, 2020;Daugaard et al, 2017;Jury et al, 2020;Dai et al, 2020;Hwang et al, 2017;Hu et al, 2020;Shafran et al, 2020]. Moreover, SLUG may be involved in feedback loops with one or more p63 isoforms [Srivastava et al, 2018;Dang et al, 2016;Herfs et al, 2010] that can also enable a partial EMT [Jolly et al, 2017a;Westcott et al, 2020]. Thus, while the proposed role of SLUG in stabilizing hybrid E/M phenotype(s) is largely robust to parametric variations, including other links and/or nodes at can alter the landscape of EMP dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of SLUG on EMP dynamics can also be influenced by upstream regulators of SLUG such as RNF8, YAP, C/EBPδ, miR-151, CBP, RCP, HDAC1, HDAC3, BRD4 and STAT3 [Cheng et al, 2020;Chesnelong et al, 2019;Kuang et al, 2020;Wang et al, 2020;Daugaard et al, 2017;Jury et al, 2020;Dai et al, 2020;Hwang et al, 2017;Hu et al, 2020;Shafran et al, 2020]. Moreover, SLUG may be involved in feedback loops with one or more p63 isoforms [Srivastava et al, 2018;Dang et al, 2016;Herfs et al, 2010] that can also enable a partial EMT [Jolly et al, 2017a;Westcott et al, 2020]. Thus, while the proposed role of SLUG in stabilizing hybrid E/M phenotype(s) is largely robust to parametric variations, including other links and/or nodes at can alter the landscape of EMP dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that the oncoprotein Src in endosomal membranes promoted exosome secretion and tumor progression [186]. Consistently, Src promotes EMT triggered by multiple EMT inducers including EGF [187], leptin [188], Cten [189], and δNp63γ [190]. Anti-EMT strategies involving targeting the TGFβ receptor or CDK2 may inhibit exosome/oncosome release from cancer cells [36].…”
Section: Exosomal Drug Resistancementioning
confidence: 93%
“…In the context of wound healing, ΔNp63α upregulates the TGF-β pathway through activation of its effectors, SMAD4 and TGF-βR2, thereby facilitating the EMT features of invasion and motility [103] In addition, silencing of the p63-regulated chromatin organizer Satb1 in SCC cells has also been shown to reverse the expression of EMT markers [104]. In another example of the importance of the relative balance of p63 isoforms, ∆Np63γ, but not ∆Np63α, can promote EMT in association with SRC-dependent transcription of Slug in HNSCC cells [105]. Overall, based on these observations, it is likely that ∆Np63α plays a critical role in EMT depending on the cell type, stage of cancer, and balance of other p63 isoforms.…”
Section: Dysregulated δNp63α Disrupts An Extensive Network Of Molementioning
confidence: 99%